Outcome of penile fracture repair – our experience (Bangladesh Journal of Urology, 2025)
Introduction: Penile fracture is an uncommon urological emergency, best managed by early surgical intervention, but the data on subsequent sexual function is sparse. This study was designed to analyse the clinical spectrum and sexual function after penile fracture repair in Urology Department of BIRDEM General Hospital and other institutes in Dhaka, Bangladesh which were attended by the authors.Materials and Methods: This is a prospective observational study extending from January 2013 to November 2024, which included all the patients admitted with the diagnosis of fracture penis. The clinical presentation, aetiology and the details of the surgical management were noted. Patients were followed‑up for 36 months. They were evaluated for the presence of penile nodules or curvature, and the erectile function was objectively recorded using the Sexual Health Inventory for Men (SHIM) questionnaire and the Erection Hardness Score (EHS).Results: During the study, 22 cases of penile fracture received treatment. Median age at injury was 29 years, and injury due to rolling over the erect penis during morning tumescence (12/22) was the most common aetiology. Ultrasound was performed in 20 patients and could detect the injury with an 80% sensitivity. All cases were repaired through a subcoronal degloving incision. Patients were followed‑up 6 monthly for 36 months.  Of the 22 patients, 18 were sexually active. The mean SHIM score was 21.36 ± 1.33 and the mean EHS was 3.21 ± 0.43. Three of the 22 patients developed penile nodule. One of them had penile curvature which was not bothersome.Conclusion: Penile fracture remains primarily a clinical diagnosis. Although prompt diagnosis and an emergent surgical exploration provides good outcomes in terms of preservation of erectile function, patients should be apprised about the problems of penile nodule and curvature.Bangladesh J. Urol. 2025; 28(1): 27-32